Optimisation of the differing conditions required for bone formation in vitro by primary osteoblasts from mice and rats - ORRISS, ISABEL R. (D.A. Spandidos, 2014)
The in vitro culture of calvarial osteoblasts from neonatal rodents remains an important method for studying the regulation of bone formation. The widespread use of transgenic mice has created a particular need for a reliable, simple method that allows the differentiation and bone-forming activity of murine osteoblasts to be studied. In the present study, we established such a method and identified key differences in optimal culture conditions between mouse and rat osteoblasts. Cells isolated from neonatal rodent calvariae by collagenase digestion were cultured for 14–28 days before staining for tissue non-specific alkaline phosphatase (TNAP) and bone mineralisation (alizarin red). The reliable differentiation of mouse osteoblasts, resulting in abundant TNAP expression and the formation of mineralised ‘trabecular-shaped’ bone nodules, occurred only following culture in α minimum essential medium (αMEM) and took 21–28 days. Dexamethasone (10 nM) inhibited bone mineralisation in the mouse osteoblasts. By contrast, TNAP expression and bone formation by rat osteoblasts were observed following culture in both αMEM and Dulbecco’s modified Eagle’s medium (DMEM) after approximately 14 days (although ~3-fold more effectively in αMEM) and was strongly dependent on dexamethasone. Both the mouse and rat osteoblasts required ascorbate (50 μg/ml) for osteogenic differentiation and β-glycerophosphate (2 mM) for mineralisation. The rat and mouse osteoblasts showed similar sensitivity to the well-established inhibitors of mineralisation, inorganic pyrophosphate (PP(i)) and adenosine triphosphate (ATP; 1–100 μM). The high efficiency of osteogenic differentiation observed following culture in αMEM, compared with culture in DMEM possibly reflects the richer formulation of the former. These findings offer a reliable technique for inducing mouse osteoblasts to form bone in vitro and a more effective method for culturing bone-forming rat osteoblasts.